Ecological Justice and the Extinction Crisis Giving Living Beings their Due - Wienhues, Anna (Bristol University Press, 2020)
As the biodiversity crisis deepens, Anna Wienhues sets out radical environmental thinking and action to respond to the threat of mass species extinction. The book conceptualises large-scale injustice endangering non-humans, and signposts new approaches to the conservation of a shared planet. Developing principles of distributive ecological justice, it builds towards a bold vision of just conservation that can inform the work of policy makers and activists. This is a timely, original and compelling investigation into ethics in the natural world during the Anthropocene, and a call for biocentric ecological justice before it is too late.